3D Printing Amorphous Polysiloxane Terpolymers via Vat Photopolymerization. Issue 4 (7th January 2019) - Sirrine, Justin M.; Zlatanic, Alisa; Meenakshisundaram, Viswanath; Messman, Jamie M.; Williams, Christopher B.; Dvornic, Petar R.; Long, Timothy E.
Abstract: Photocuring and vat photopolymerization (VP) additive manufacturing (AM) is reported for two families of fully amorphous poly(dimethyl siloxane) (PDMS) terpolymers containing either diphenylsiloxy (DiPhS) or diethylsiloxy (DiEtS) repeating units. A thiol‐functionalized PDMS crosslinker enables rapid crosslinking in air using efficient thiol–ene addition. Differential scanning calorimetry and dynamic mechanical analysis (DMA) confirm the absence of crystallinity for the DiPhS‐containing systems, while DMA shows a rubbery plateau extending to greater than 200 °C for the DiEtS‐containing system. VP‐AM of both photopolymer systems afford well‐defined 3D geometries, including high aspect ratio structures, which demonstrate feasibility of these photopolymers for the 3D printing of unique geometric objects that require elastomeric performance to temperatures as low as −120 °C. Abstract : Vat photopolymerization additive manufacturing with vinyl‐functional siloxane terpolymers and a thiol‐functional siloxane, enable thiol–ene addition for rapid crosslinking in the presence of air. Thermal analysis confirms the absence of crystallinity, and dynamic mechanical analysis displays a rubbery plateau width of more than 200 °C. These photopolymer compositions hold promise for 3D printed elastomers that offer temperature‐independent moduli from room temperature to −120 °C.